Respuesta de la fibrina rica en plaquetas en la preservación del reborde alveolar. Revisión narrativa (2021)
Platelet-rich fibrin is a second-generation autologous material of platelet concentrates, with simplified processing and without biochemical manipulation of blood around 4 fundamental events of healing, angiogenesis, immune control, trapping of circulating stem cells and epithelialization that covers the wound. In order to enhance vertical and horizontal alveolar preservation after tooth extraction.